'Stay home you murderer!': populist policing of COVID-19 in Italy. (September 2021) - Scalia, Vincenzo
Italy was the first European country to experience the impact of COVID-19. In order to deal with the health emergency, in early March 2020, the Italian government enforced strict lockdown measures. The different Italian police forces, the Polizia di Stato, Carabinieri and city police forces (Polizia Municipale), patrolled the streets, ensuring that people stayed at home and non-essential shops remained closed. These police forces received unprecedented support from the public in enforcing lockdown. People were active in their neighbourhoods, taking pictures of alleged violators and reporting them to the police, as well as posting pictures of those violating the rules on social networks. Local administrators encouraged citizens to report lockdown violations and in the case of Rome, introduced an online reporting system. This article focuses on the policing of lockdown in Italy. The article develops the argument that public attitudes, defined as policing from below, combined with policing from above by local administrators, produced a populist policing of the lockdown. Qualitative methodology is used to discuss interviews with police officers and analyse newspaper articles. Populist political forces are hegemonising in Italy, relying on the feelings of insecurity that the virus has embittered. Populist hegemony strongly influenced the policing of problems related to COVID. The lack of community policing or plural policing models within the organisation of Italian police forces, which remain a combination of continental and colonial models, has been decisive in the development of populist policing. The consequence of this is a type of 'policing on demand', with the public providing the police with intelligence and demanding enforcement.